Predictors of coronary artery calcium among 20-30-year-olds: The Coronary Artery Calcium Consortium. (May 2020) - Osei, Albert D.; Uddin, S.M. Iftekhar; Dzaye, Omar; Achirica, Miguel Cainzos; Dardari, Zeina A.; Obisesan, Olufunmilayo H.; Kianoush, Sina; Mirbolouk, Mohammadhassan; Orimoloye, Olusola A.; Shaw, Leslee; Rumberger, John A.; Berman, Daniel; et al.
Abstract: Background and aims: We sought to understand the risk factor correlates of very early coronary artery calcium (CAC), and the potential investigational value of CAC phenotyping in adults aged 20–30 years. Methods: We studied all participants aged 20–30 years at baseline (N = 373) in the Coronary Artery Calcium Consortium, a large multi-center cohort study of patients aged 18 years or older without known atherosclerotic cardiovascular disease (ASCVD) at baseline, referred for CAC scoring for clinical risk stratification. We described the prevalence of CAC in men and women, the frequency of risk factors by the presence of CAC (CAC = 0 vs CAC >0), and assessed the association between traditional non-demographic CVD risk factors (hypertension, hyperlipidemia, smoking, family history of CHD, and diabetes) and prevalent CAC, using age- and sex-adjusted logistic regression models. Results: The mean age of the study participants was 27.5 ± 2.4 years; 324 (86.9%) had CAC = 0, and 49 (13.1%) had CAC >0. Among the 49 participants with CAC, 38 (77.6%) were men, and median CAC score was low at 4.6. In age- and sex-adjusted models, there was a graded increase in the odds of CAC >0 with increasing traditional cardiovascular disease (CVD) risk factor burden ( p  = 0.001 for linear trend). Participants with ≥3 traditional risk factors had a statistically significant higher odds of having prevalent CAC (OR 5.57, 95% CI; 1.82–17.03) compared to participants with no risk factors. Conclusions: Our study demonstrates the non-negligible prevalence of CAC among very high-risk young US adults, reinforcing the critical importance of traditional risk factors in the earliest development of detectable subclinical ASCVD. Graphical abstract: Image 1 Highlights: Coronary Artery Calcium (CAC), a direct marker of coronary atherosclerosis, is an important risk stratification tool. Almost no data are available on the determinants of CAC among very young adults <30 years. These findings reinforce the importance of traditional risk factors in the development of detectable subclinical ASCVD.